A feedback loop between CaWRKY41 and H2O2 coordinates the response to Ralstonia solanacearum and excess cadmium in pepper. (14th January 2019) - Dang, Fengfeng; Lin, Jinhui; Chen, Yongping; Li, Gui Xin; Guan, Deyi; Zheng, Shao Jian; He, Shuilin
Abstract : CaWRKY41 plays dual roles in increasing resistance to Ralstonia solanacearum infection and susceptibility to Cd stress in pepper by indirectly and directly increasing H2 O2 accumulation and Zn transporter expression. Abstract: WRKY transcription factors have been implicated in both plant immunity and plant responses to cadmium (Cd); however, the mechanism underlying the crosstalk between these processes is unclear. Here, we characterized the roles of CaWRKY41, a group III WRKY transcription factor, in immunity against the pathogenic bacterium Ralstonia solanacearum and Cd stress responses in pepper ( Capsicum annuum ). CaWRKY41 was transcriptionally up-regulated in response to Cd exposure, R. solanacearum inoculation, and H2 O2 treatment. Virus-induced silencing of CaWRKY41 increased Cd tolerance and R. solanacearum susceptibility, while heterologous overexpression of CaWRKY41 in Arabidopsis impaired Cd tolerance, and enhanced Cd and zinc (Zn) uptake and H2 O2 accumulation. Genes encoding reactive oxygen species-scavenging enzymes were down-regulated in CaWRKY41 -overexpressing Arabidopsis plants, whereas genes encoding Zn transporters and enzymes involved in H2 O2 production were up-regulated. Consistent with these findings, the ocp3 ( overexpressor of cationic peroxidase 3 ) mutant, which has elevated H2 O2 levels, displayed enhanced sensitivity to Cd stress. These results suggest that a positive feedback loop between H2 O2 accumulation and CaWRKY41 up-regulation coordinates the responses of pepper to R. solanacearum inoculation and Cd exposure. This mechanism might reduce Cd tolerance by increasing Cd uptake via Zn transporters, while enhancing resistance to R. solanacearum .